ETNOMATEMATIKA JUDI MOMONGAN (Melestarikan Bahasa Bali dengan Mengenalkan ”Kruna Wilangan” dalam Pembelajaran Matematika ) - Made Ari Purwadi (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
AbstractThis ethnomathematics exploration research was aimed at determining the mathematical concepts in the momongan (dice) games and the implementation in the mathematics learning. This qualitative research used an ethnographic approach using human instruments. The research data obtained through observation activities, ethnographic records, interviews and implementation notes with a dealer and two players and 21 students in grade VIII of SMP Laboratorium Undiksha Singaraja who act as research subjects. The research result shows that in the game can be obtained the application of number operations, social arithmetic, probability, and jargon in counting number. Keywords: ethnomathematics, momongan, integer operations, social arithmetic, probability.